Total antioxidant response in patients with schizophrenia - Ustundag, Bilal; Atmaca, Murad; Kirtas, Ozlem; Selek, Sahabettin; Metin, Kerem; Tezcan, Ertan (Wiley, 2006)
There is a large amount of convincing data demonstrating that reactive oxygen species (ROS) are involved in initiation and development of many different forms of neuropsychiatric disorders. The levels of oxidants and antioxidants in schizophrenia have been evaluated. However, measurements of total antioxidant response (TAR) were not evaluated up to now. Therefore, the objectives of this study are to investigate plasma TAR levels in schizophrenia subtypes. A total of 76 patients with schizophrenia and 25 healthy volunteers were included in the study. Positive and Negative Syndrome Scale (SANS and SAPS, respectively) were applied to patients. TAR values were determined in the plasma of normal healthy controls and patients with schizophrenia. Plasma TAR levels of each schizophrenia subtype were significantly lower than healthy controls (P < 0.01 for disorganized, residual and undifferentiated subtypes and P < 0.01 for paranoid subtype). When intragroup comparisons were performed, paranoid subtype had higher plasma TAR levels compared to other subtypes (P < 0.01). Accordingly, as a whole group, patients with schizophrenia had lower plasma TAR levels compared to controls. Plasma TAR levels were significantly and negatively correlated with SANS scores, and duration of illness was evaluated but not related to other parameters. Consequently, the present study further emphasizes the growing consideration that free radical damage may have an important etiopathogenetic role on the development of schizophrenia and suggests that decreased plasma total antioxidant levels may be related to the progression of illness.
Keywords: paranoid; residual; schizophrenia; total antioxidant response